Constructive campaigning for autism services : the PACE parents' handbook - Wason, Armorer (Jessica Kingsley, 2005)
Parents of children with autism know better than anyone else what educational and public services their child needs. They also know the deficiencies of the system and the frustrations encountered while trying to obtain such services. Constructive Campaigning for Autism Services is an essential guide to effective campaigning for appropriate services for children with autism, written by PACE (The Parents' Autism Campaign for Education). Based on the real-life experiences, dilemmas and questions of parents themselves involved in campaigning, this practical handbook explains how the system works b.